Incorporation of Exogenous Fatty Acids Protects Enterococcus faecalis from Membrane-Damaging Agents - Saito, Holly E. (American Society for Microbiology, 2014)
Enterococcus faecalis is a commensal bacterium of the mammalian intestine that can persist in soil and aquatic systems and can be a nosocomial pathogen to humans. It employs multiple stress adaptation strategies in order to survive such a wide range of environments. Within this study, we sought to elucidate whether membrane fatty acid composition changes are an important component for stress adaptation. We noted that E. faecalis OG1RF was capable of changing its membrane composition depending upon growth phase and temperature. The organism also readily incorporated fatty acids from bile, serum, and medium supplemented with individual fatty acids, often dramatically changing the membrane composition such that a single fatty acid was predominant. Growth in either low levels of bile or specific individual fatty acids was found to protect the organism from membrane challenges such as high bile exposure. In particular, we observed that when grown in low levels of bile, serum, or the host-derived fatty acids oleic acid and linoleic acid, E. faecalis was better able to survive the antibiotic daptomycin. Interestingly, the degree of membrane saturation did not appear to be important for protection from the stressors examined here; instead, it appears that a specific fatty acid or combination of fatty acids is critical for stress resistance.